EVALUATION OF PUBLIC TRANSPORT FACILITIES AT PORTS, AIRPORTS, STATIONS, AND TERMINALS (Jurnal Pensil : Pendidikan Teknik Sipil, 2024)
Abstract Indonesia is known as the "Land of Islands" because it has thousands of islands scattered from Sabang to Merauke. To connect various regions or islands, Indonesia has a diverse range of public transportation modes. Facilities in public transportation must be adequate to accommodate prospective passengers traveling to a particular area. Evaluation of public facilities is essential to enhance the comfort of passengers. This research was conducted using direct observation methods and literature reviews from sources available on the internet. In this study, several public transportation modes are discussed, namely Ketapang Port, I Gusti Ngurah Rai Airport, Bandung Station, and Guntur Melati Terminal. Ketapang Port has some shortcomings, including the need for improvement in weather information systems, operational traffic system enhancement, service improvement, and expansion of the dock. Meanwhile, I Gusti Ngurah Rai Airport has a deficiency in the VVIP parking area, requiring improvement. According to Minister of Transportation Regulation No. 63 of 2019, Bandung Station lacks aspects related to safety, security, comfort, and convenience. Terminal Guntur Melati, as per Minister of Transportation Regulation No. 40 of 2015, faces deficiencies in safety and convenience aspects. Keywords: Facilities, Public Transportation, Evaluation